Pendidikan Anak Usia Dini dalam Perspektif Kebijakan Daerah: Studi atas Perda Kota Pariaman - Amira Azmi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Early Childhood Education (PAUD) is an important aspect in developing quality human resources. In the context of regional policy, regulations governing PAUD have a strategic role in ensuring the accessibility and quality of education for children. This research aims to analyze the implementation of the Regional Regulations (Perda) of Pariaman City regarding PAUD, as well as examine its influence on improving the quality of children's education in the area. Using a regional policy study approach, this research explores how the regional regulation is implemented, the challenges faced in its implementation, and its impact on the success of the PAUD program in Pariaman City. The research results show that although the PAUD Regional Regulation provides a strong legal basis, its implementation is still hampered by human resource factors, budget, and coordination between related agencies. However, this policy still has a positive impact, especially in increasing the number of affordable PAUD facilities and increasing public awareness of the importance of education at an early age. This research provides recommendations for improvements in the implementation of the PAUD Regional Regulation in order to achieve more optimal educational goals in Pariaman City.